Optimisation of Genetic Transformation Parameters Through Microprojectile Bombardment Using Green Fluorescent Protein Reporter System in Dendrobium ‘Sonia 17’ Callus - Tee, Chong Siang (2004)
Dendrobium ‘Sonia 17’ was used for this study as it is one of the common Dendrobium hybrids grown for cut-flower market in Malaysia. Different concentrations of auxins (picloram, dicamba and 2,4-D) were investigated for the effectiveness of inducing callus. Callus was successfully induced in the dark in all types of media studied, however, 2,4-D was ineffective in callus induction. Calluses induced from the protocorm-like-bodies (PLBs) were used as the potential target tissues for genetic transformation. Three types of morphologically distinct callus were identified (types A, B and C) from 50 μM picloram-containing half strength Murashige and Skoog (MS) medium (type C callus) and phytohormone-free half strength MS medium (types A and B callus). Morphologically, type A callus is a mixture of compact and friable tissues, type B callus is comprised of nodal shape tissues and type C callus has a more variable shape. Regeneration studies of these calluses were carried out to examine the effect of different cytokinins concentrations (zeatin, kinetin, BA) on the plant regeneration frequency. It was found that Dendrobium ‘Sonia 17’ plant regeneration for callus was a very slow process, after four months, and the regeneration frequency was approximately 28 % (type A callus), 20 % (type B callus) and 12 % (type C callus) in the phytohormone-free medium. Different hygromycin concentrations were used to investigate the sensitivity of different potential target tissues. The determined hygromycin concentrations that could effectively inhibit or kill the tissues were determined at 25 mg/L for type A callus, 20 mg/L for type B callus, 10 mg/L for type C callus and 25 mg/L for PLBs. In investigating the genetic transformation system for Dendrobium ‘Sonia 17’, the green fluorescent protein (GFP) was chosen as the reporter system. The GFP transient expression characteristics were observed and the highest GFP transient expression in all the explants types bombarded and plasmid types examined was on day two post-bombardment. Based on the results obtained and observations carried out, types A and B callus were chosen as the potential target tissues and the 35S- SGFP-TYG-nos GFP plasmid was chosen and used for the genetic transformation study of Dendrobium ‘Sonia 17’. Both GFP and β-glucuronidase (GUS) reporter systems were used to optimised the bombarment parameters to increase the reliability and accuracy of the co-transformation system. Expressions of GFP and GUS genes were both driven by 35S promoter from two different plasmids, p35S and pSMDFR respectively. Bombardment parameters was optimised for both type A callus (1100 psi, 6 cm target distance, 1.0-μm gold particle size, 0.4 μg plasmid DNA per bombardment, 1:1 co-bombardment plasmid DNA ratio and two days pre-bombardment sub- culture duration) and type B callus (650 psi, 6 cm target distance, 1.0-μm gold particle size, 0.4 μg plasmid DNA per bombardment, 1:1 co-bombardment plasmid DNA ratio and two days pre-bombardment sub-culture duration). In addition, GFP was observed to have higher expression frequency in both types A and B callus in all the parameters investigated compared to the GUS system indicating the GFP system could be used as a reporter system in this co-bombardment study. The non- destructive and rapid GFP monitoring system is a better reporter system than the conventional GUS reporter system. The bombarded callus tissues were transferred to the hygromycin-containing selection medium. After a month of culturing in the selection medium, only the putative transformed tissues were able to survive and proliferate. Four putative transformant lines were isolated and the transformation efficiency was 1.7 %. At the same time GFP and GUS were used to investigate the expression of the genes. All putative transformed lines were subjected to the molecular analyses. Insertion of the transgenes (gfp, gusA and hptII genes) into the genome was confirmed using (polymerase chain reaction) PCR, Southern blot and DNA sequencing. PCR analysis showed co-transformation frequency of the un-linked genes from different plasmids was 66 %. Besides, GFP was used to monitor the expression patterns of the transformed tissues and the transformed lines were able to multiply and regenerate into plantlets.